Genetic influence on auditory information processing in schizophrenia: P300 in monozygotic twins - Weisbrod, Matthias; Hill, Holger; Niethammer, Rainer; Sauer, Heinrich (Biological psychiatry, 1999)
Background: It is widely accepted that schizophrenia is to some extent genetically determined. Abnormalities of the P300 component are one of the most robust biological findings in schizophrenia. They outlast clinical impairment and are present also in relatives of schizophrenic patients. In the present study on schizophrenic twins, the heritability of auditory P300 abnormalities and the influence of task difficulty on heritability was examined. Methods: Twenty-two monozygotic twin pairs were included into this study (eight pairs discordant, five pairs concordant for schizophrenia or schizoaffective psychosis according to ICD-10 criteria, and nine control pairs). Two different versions of the auditory oddball paradigm were used to control for deficient stimulus perception. Results: Compared to healthy controls, P300 amplitudes were significantly smaller in affected twins as well as in the non-affected co-twins of the discordant pairs. Conclusions: Our results suggest that P300 amplitude reduction is a genetically transmitted vulnerability marker for schizophrenia. Because the findings were independent of the difficulty of the task and could be demonstrated even when pitch disparity was adjusted to the subjects’ ability to discriminate tones, the findings can not be explained by deficient perception and may rather be related to the genetic influence on higher information processing.
Gesehen am 02.02.2021